Conceptualizing and Contextualizing Time and Other Utterances in Cameroon: A Linguistic Perspective - Ngha Fuh Nji, Joefrey; Zaoussou, Eugene Kolaouna (International Journal of Linguistics, 2025)
Purpose: This study explores the conceptualization and contextualization of time in Cameroon from a linguistic perspective, emphasizing how localized meanings of words and expressions shape cognitive and social dynamics. Methodology: Anchored in the pragmatic framework which examines the relationship between linguistic signs, their users, and speaker intent, this research focuses on the role of context, place, and time in the production and interpretation of time-related utterances. Data was drawn from casual conversations, lecture materials, and media discourse. Findings: The study reveals that Cameroonian linguistic practices reflect a strong emphasis on hierarchical status, relatively low prioritization of time-consciousness, and the adaptation of certain expressions in ways that diverge from their conventional meanings in other cultural settings. Unique Contribution to Theory, Practice and Policy: These findings suggest that time perception in Cameroon is deeply embedded in socio-cultural realities, with significant implications for communication, governance, and national development. Encouraging greater time-consciousness, particularly among the ruling class, could contribute to enhanced efficiency and progress across various sectors.